Pengaruh Brand Ambassador Dan Tagline “Gratis Ongkir” Shopee Terhadap Keputusan Pembelian - Efdison, Zefri; Efridozel, Rahul; Fitriya, Sri; Yadewani, Dorris; Harahap, Erni Febrina (Gapenas Publisher, 2025)
In the modern era, society's dependence on technology, particularly the internet, has brought significant changes in lifestyle, including shopping behavior. E-commerce, as a form of electronic commerce, is rapidly evolving as a mechanism for exchanging goods and services over the internet. This study aims to measure the influence of brand ambassadors and the